2008
DOI: 10.1161/atvbaha.108.167437
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the IL1-Receptor Antagonist Gene ( IL1RN ) Are Associated With Multiple Markers of Systemic Inflammation

Abstract: Background— Circulating levels of acute phase reactant proteins such as plasma C-reactive protein (CRP) are likely influenced by multiple genes regulating the innate immune response. Methods and Results— We screened a set of 16 inflammation-related genes for association with CRP in a large population-based study of healthy young adults (n=1627). Results were validated in 2 independent studies (n=1208 and n=4310),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 29 publications
1
60
2
Order By: Relevance
“…Additionally, they found that the IL1RN 1018 haplotype was associated with increased concentrations of IL-1b and IFN-g. These findings were recently confirmed by a study that used three independent cohorts comprising elderly individuals, young adults, and adults with severe carotid disease (16). We hypothesized that the IL1RN gene may impact on disease severity and survival in invasive pneumococcal disease through modulation of IL-1Ra levels.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, they found that the IL1RN 1018 haplotype was associated with increased concentrations of IL-1b and IFN-g. These findings were recently confirmed by a study that used three independent cohorts comprising elderly individuals, young adults, and adults with severe carotid disease (16). We hypothesized that the IL1RN gene may impact on disease severity and survival in invasive pneumococcal disease through modulation of IL-1Ra levels.…”
mentioning
confidence: 59%
“…Our data differ from those of Rafiq et al (15) and Reiner et al (16), who demonstrated that the C allele was associated with reduced IL-1Ra concentrations in elderly individuals, young adults, and adults with severe carotid artery disease. The subjects in Rafiq's and Reiner's studies (15,16) were healthy adults with measurements made after an overnight fast. In contrast, our subjects were children and adults in sub-Saharan Africa, with a severe acute illness, or a chronic viral infection, both of which are associated with a high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In this same cohort of patients, we found that single nucleotide polymorphisms (SNPs) in genes that regulate inflammation were also associated with PSF [73]. Specifically, we found that PSF was associated with the C allele of IL1RN rs4251961, which is commonly associated with a decrease in IL-1ra and an increase in proinflammatory cytokines like IL-1β and CRP [74,75]. Further, we found that functional polymorphisms in Toll-like receptor 4 (TLR4) that render it less responsive to its ligands were associated with less fatigue [73].…”
Section: Inflammation and The Biological Basis Of Psfmentioning
confidence: 78%
“…P=0.037 a b Fig. 3 Poststroke fatigue is more prevalent in those with the C allele of IL1RN (a), which is generally associated with increased inflammation [74,75], and less prevalent in those with single nucleotide polymorphisms (SNPs) in TLR4 (b) that render the Toll-like receptor less sensitive to its agonists. FAS Fatigue Assessment Scale…”
Section: Therapeutic Approaches To the Treatment Of Depression: A Focmentioning
confidence: 99%
“…In our study the mutant homozygote for MTHFR C677T is 9.5%, 9.5%, 16.9%, and the T allele frequency is 26%, 29% and 40%, respectively for control subjects, patients with SAP and ACS. There is only a (27,37). ILRa genotypes BB, BC, BD and DD were significantly more frequent among patients with SAP and ACS compared to control subjects (Table 2, P1=0.002 and P2=0.009).…”
Section: Resultsmentioning
confidence: 95%